Strategic Optimization of Village Cooperatives for Economic Sovereignty and Poverty Alleviation: A Case Study of Sindangpakuon Village - Fadilla, Febrynahl Fitra (International Journal of Research in Community Services, 2026)
The purpose of this study is to investigate the structural reform of economic institutions at the village level, with Sindangpakuon Village serving as the primary case study. This is done with the intention of reducing poverty. Even though Indonesia has undergone a significant amount of decentralisation, a great number of rural areas continue to be trapped in cycles of economic dependence. As a result of the widespread presence of exploitative informal lending, which is commonly referred to as "Bank Emok" in the community, the situation has become drastically worse. Within the framework of the "Lentera Desa" community service framework, this study utilised a Business Process Reengineering (BPR) approach to conduct an analysis of the inefficiencies that are currently being experienced by Village-Owned Enterprises (BUMDes) and Village Cooperatives (KOPDes). In order to compete with informal lenders, the intervention built a distribution structure known as "Hub and Spoke" as well as computerised loan procedures. Sindangpakuon is in high demand from industrial supply chains; yet, the findings reveal that impediments impeding capital accumulation stem from weak institutional synergy and onerous administrative procedures. This is despite the fact that Sindangpakuon is in widespread demand. The purpose of this article is to offer an integrated ecosystem in which the cooperative serves as the retail and financial nexus, bringing together products from BUMDes and local Micro, Small, and Medium Enterprises (MSMEs). It is suggested that there is an interrelated ecology. It should come as no surprise that strategic alignment with the national plan of "Koperasi Desa Merah Putih" provides the essential regulatory and financial leverage in order to achieve long-term independence. Based on the findings, it appears that increasing openness through the use of digital dashboards and lowering the barriers to transaction can greatly increase community participation in villages that are located in close proximity to industrial areas. This provides a model that can be replicated in order to achieve economic autonomy in those areas that are rural.